Comparison of growth and nutritional status of Chinese and Japanese children and adolescents. (3rd July 2020) - Yin, Xiaojian; Yang, Xiaofang; Ji, Liu; Song, Ge; Wu, Huipan; Li, Yuqiang; Sun, Yi; Bi, Cunjian; Li, Ming; Zhang, Ting; Kato, Hiroshi; Akira, Suzuki; et al.
Abstract: Background: The difference in growth and nutritional status, both important indices of population quality, between Chinese and Japanese children and adolescents is unknown. Aim: This study aimed to compare growth and nutritional status between Chinese and Japanese children and adolescents. Subjects and methods: The height-for-age and BMI-for-age distribution of 9, 226 children and adolescents aged 7–18 years from China and Japan were described with the Lambda Mu and Sigma method. Wasting, overweight and obesity were evaluated based on BMI-for-age cut-offs of the 2007 WHO Child Growth Reference. Results: For boys, the overall average height, weight and BMI of Chinese participants were 3.0 cm, 4.8 kg and 1.2 kg/m 2 greater compared with Japanese participants, respectively; for girls, these were 4.6 cm, 3.9 kg and 0.6 kg/m 2, respectively. Compared with Japanese children, the 3rd, 50th and 97th percentiles of height-for-age, 1 Z -score, and 2 Z -score of BMI-for-age of Chinese children were greater, whereas the minus 2 Z -scores of Chinese children were less. The prevalence of wasting, overweight and obesity among Chinese participants was greater. Conclusions: Compared with Japanese children, Chinese children tended to be taller. The worrying burden of overweight, obesity and wasting was recognised among Chinese children.